The economic problems of Argentina between the dictatorship (1976-1983) and democracy (1983-1989): review of the heterodox literature and its main contributions (Ágora de Heterodoxias, 2021)
This review article aims to make a synthesis of the different economic problems that, developed during the last dictatorship (1976-1983), meant an important limitation for the years of the democratic transition (1983-1989) in Argentina. The approach is carried out recovering different positions and debates of the main investigations that focused on analyzing the economic transformations operated in the analyzed stage with a heterodox perspective. It proceeds by making a cross between said economic and historical contributions seeking to reconstruct the limitations of the economic system during the democratic inheritance around 1983. To do this, it stopped at the examination of different problems related to the external public debt, the alterations in the financial system and the unequal transfer of income, among other discussions. It was found that there is a significant consensus that ensures that the transformations operated in the economy at this stage, especially during the dictatorial regime of 1976, altered the country's accumulation regime. And that the irregularities that characterized it from then on hardly allow dismissing the period of dictatorship as one more stage in the national economic history, resignifying it finally as a historical turning point
Keywords: inflation; public debt; democracy; macroeconomics; monetary policy